Trade relations between Colombia and the Czech Republic : Business opportunities - Lukeš, Nataly (2016)
The goal of this thesis is to determine and analyze trade relations between the Czech Republic and Colombia and to identify concrete business opportunities among them. the sub goals include the comparison of macroeconomic, political and socioeconomic indicators, analysis of the trade flows of goods, to identify the top 10 products and to determine the competitive advantage of both countries by using Porter's model of national competitive advantage. Finally several business opportunities are identified and each of them is described in more detail. The used methods are description, analysis and comparison of data from the Trademap webpage, World Bank and official records and reports from both countries trade ministries.